Where are Map Libraries Heading? Some Route Maps for the Digital Future - Campbell, Tony (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2000)
The metaphorical route maps I shall be offering will be highly selective, and sometimes personal. But I shall try to raise fundamental issues that I believe are relevant for all map libraries. Given the mixed nature of this audience, I hope that what I have to say may have some interest for those who are deprived of the enjoyment of handling maps. Much of what I say will relate to the Internet. ‚Maps and the Internet‘ is the focus for a growing number of symposia. Recently, the British Ordnance Survey hosted a three-day meeting of 25 European countries on just this subject. We have, quite rightly, talked a lot about the Web this week.